1988
DOI: 10.1093/jnci/80.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flavone Acetic Acid on Lewis Lung Carcinoma: Evidence for an Indirect Effect1

Abstract: Flavone-8-acetic acid (FAA), a new antitumor agent currently undergoing clinical trial, fails to inhibit the growth of early stage Lewis lung (LL) tumors growing in the lung. However, the growth of advanced subcutaneous tumors, arising from inoculation of either the original in vivo LL line or a tissue culture-adapted cell line (LLTC) derived from the LL line was delayed significantly by FAA treatment. Comparison, by clonogenic survival assays, of the cytotoxic effect of FAA on LLTC cells demonstrated that mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Although a slightly longer time was required for tumours to become palpable, the tumour volumes were not significantly smaller than those in the control mice (Figure 3). Lewis lung tumours (Finlay et al, 1988) were found to grow equally well in naive control mice or euthymic or T x B mice which had previously been cured of a Colon 38 tumour (data not shown).…”
mentioning
confidence: 88%
“…Although a slightly longer time was required for tumours to become palpable, the tumour volumes were not significantly smaller than those in the control mice (Figure 3). Lewis lung tumours (Finlay et al, 1988) were found to grow equally well in naive control mice or euthymic or T x B mice which had previously been cured of a Colon 38 tumour (data not shown).…”
mentioning
confidence: 88%
“…It has been suggested that the site of the tumour is important in determining its responsiveness to FAA (Bibby et al, 1989b). Finlay et al (1988) found that small lung metastases of the Lewis lung tumour failed to respond to FAA treatment, while larger lung nodules and subcutaneous implants of this tumour were sensitive. To determine the role of the vasculature in the anti-tumour action of FAA, we have examined the process of attachment and vascularisation of EMT6 spheroids in the peritoneum, and found tumours which were directly comparable in site and size range to avascular spheroids (AVS).…”
mentioning
confidence: 95%
“…This experimental agent is continuing to generate interest despite disappointing results in clinical trials (Kerr et al, 1989) because it appears to act via a novel, indirect mechanism. The low cytotoxicity of FAA against cell lines from FAA-responsive tumours (Finlay et al, 1988), suggests that its antitumour effect involves some interaction with host tissues. FAA affects both tumour structure and physiology, including haemorrhagic necrosis (Smith et al, 1987), a fall in ATP levels (Evelhoch et al, 1988), and a decrease in blood flow (Evelhoch et al, 1988;Bibby et al, 1989a).…”
mentioning
confidence: 99%
“…Immunosuppression interfered with the anti-tumour action of endotoxin in spite of the fact that haemorrhagic necrosis still occurred. Response of human tumour xenografts to FAA appears to be modest (Giavazzi et al, 1988;Finlay et al, 1988;H. Fiebig personal communication) and there are certainly no published data demonstrating spectacular responses similar to those achieved in subcutaneous murine tumours.…”
mentioning
confidence: 99%